Chemical genetic approach using β-rubromycin reveals that a RIO kinase-like protein is involved in morphological development in Phytophthora infestans - Shuji Tani (Nature Portfolio, 2020)
Abstract To characterize the molecular mechanisms underlying life-stage transitions in Phytophthora infestans, we initiated a chemical genetics approach by screening for a stage-specific inhibitor of morphological development from microbial culture extracts prepared mostly from actinomycetes from soil in Japan. Of the more than 700 extracts, one consistently inhibited Ph. infestans cyst germination. Purification and identification of the active compound by ESI–MS, 1H-NMR, and 13C-NMR identified β-rubromycin as the inhibitor of cyst germination (IC50 = 19.8 μg/L); β-rubromycin did not inhibit growth on rye media, sporangium formation, zoospore release, cyst formation, or appressorium formation in Ph. infestans. Further analyses revealed that β-rubromycin inhibited the germination of cysts and oospores in Pythium aphanidermatum. A chemical genetic approach revealed that β-rubromycin stimulated the expression of RIO kinase-like gene (PITG_04584) by 60-fold in Ph. infestans. Genetic analyses revealed that PITG_04584, which lacks close non-oomycete relatives, was involved in zoosporogenesis, cyst germination, and appressorium formation in Ph. infestans. These data imply that further functional analyses of PITG_04584 may contribute to new methods to suppress diseases caused by oomycetes.